2007
DOI: 10.1093/bja/aem272
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase reduces local anaesthetic volumes for sub-Tenon’s anaesthesia

Abstract: Hyaluronidase permits a significant 2.4-fold (95% CI, 1.8-3.4) reduction in MLAV for sub-Tenon's anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 23 publications
0
23
0
2
Order By: Relevance
“…Schulenburg et al 24 performed a double-blind RCT using a minimum local anaesthetic volume (MLAV) design. Patients received a sub-Tenon's 2% lignocaine injection with or without 15 IU ml −1 hyaluronidase.…”
Section: Hyaluronidasementioning
confidence: 99%
“…Schulenburg et al 24 performed a double-blind RCT using a minimum local anaesthetic volume (MLAV) design. Patients received a sub-Tenon's 2% lignocaine injection with or without 15 IU ml −1 hyaluronidase.…”
Section: Hyaluronidasementioning
confidence: 99%
“…Quality of anaesthesia, akinesia and duration of sub-Tenon's block may be affected by the size of globe, size of orbital cavity, local anaesthetic agent, volume, adjuvant administration and the use of intraocular pressure lowering device after the block [16,17]. Sub-Tenon's block is known to be effective but frequent intraoperative supplementary injections are required.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of anesthesia can be extended by simply injecting additional local anaesthetic agent through the initial dissection midway through the procedure on the operating table by the operating surgeon under sterile conditions [1]. Anaesthesia, akinesia and duration of sub-Tenon's block may be affected by several factors including the size of globe, orbital cavity, anaesthetic agent, volume, adjuvant and intraocular pressure lowering device [16,17]. There are wide variations in the volume of local anaesthetic agent used which ranges from 4 -10 mls [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are some reports of HA as an adjunctive in RA for ophthalmic surgery improving the efficacy and speed of nerve blocks [14][15][16][17][18][19][20], other authors do not report any beneficial effect of adjunctive HA [21][22][23]. Interestingly, Schulenburg et al [24] concluded that HA reduces the volumes needed for local anaesthesia. In addition, careful review of the literature revealed that HA has added value in terms of efficacy and speed of the anaesthesia and avoids a significant increase in intraocular pressure when small volumes (5-8 ml) are used [14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%